Pengaruh Lingkungan Kerja, Leader Member Exchange dan Budaya Kaizen Terhadap Kinerja Karyawan PT Yamaha Music Manufacturing Asia Section Mechanical Part Grup Painting Printing - Rahayu, Martiana Putri; Hanafia, Fifi (Universitas Mercu Buana, 2025)
Employee performance is essential to supportithe successiof the organization amidst the iincreasingly tight icompetition in musical instrument production andi the iemergence of imany new competitors. The era of globalization brings various challenges and opportunities, which affect the way employees work and contribute to the company. Thisistudy aimsi to determinei how muchiinfluence the iWork Environment, Leader Member Exchange and Kaizen Culture have on Employee Performance in the Mechanical Part Section of the PaintingiPrinting Group of iPT Yamaha iMusic iManufacturing Asia. Thei population iof this istudy wasiall employees iof the mechanical part section of the paintingiprinting group production totaling 65ipeople. The samplingitechnique used was nonprobability sampling iused in ithis study iwas fed up. This study used a quantitative method through a survey using a questionnaire for theiresearch instrumentiusing a Likert scale. Theidata analysis methodiused was validity testing, reliability testing, classicali assumption testing, imultiple linearianalysis and hypothesisitesting. Testing was carriediout using IBMiSPSS StatisticsiVersion 26i (SPSS 26). The results of the study showed that the Work Environment, Leader Member Exchange and Kaizen Culture had a partial effect.